Competition and facilitation determine dwarf mistletoe infection dynamics - Queijeiro-Bolaños, Mónica E.; González, Edgar J.; Martorell, Carlos; Cano-Santana, Zenón (The Journal of ecology, 2017)
1. Interspecific interactions have a fundamental role in plant population dynamics, as they may set the conditions for species coexistence. Parasitic plants, like dwarf mistletoes, offer the opportunity to study competition for resources that are different from those consumed by most plants, allowing for a better understanding of the interaction. 2. We explored how interspecific interactions between two dwarf mistletoe species (Arceuthobium), co-infecting the same host species (even sharing the same individual tree of Pinus hartwegii) affect their infection dynamics at two different stages of population development (colonization of new hosts and subsequent growth), and if heterogeneity in resource availability (host density and size structure) affects these interactions. For that purpose, we integrated these processes into a spatially explicit model of density-dependent population growth. 3. We found that self-regulation (density-dependence) was strong for both species; however, the intensity and sign of interspecific interactions changed depending on host size and demographic process. Population growth in Arceuthobium globosum was reduced by competition, except for smaller hosts where A. globosum growth was facilitated by Arceuthobium vaginatum. Arceuthobium vaginatum was facilitated by A. globosum regardless of host size. Colonization of new hosts by A. globosum was enhanced by previous infection by the other species, showing intraguild facilitation. 4. Demographic importance of interactions depended on stand structure: in homogeneous, low-density forests, facilitation predominates, increasing the population sizes of both species, whereas the opposite occurs in heterogeneous and dense forests. Both species achieved stable coexistence, fulfilling the invasibility criterion because each mistletoe species can invade a forest that is already infected by the other species. 5. Synthesis. Despite the fundamentally different mechanisms underlying the interactions between mistletoes compared with non-parasitic plants, our results reveal that their behaviour at the population level is similar. Stabilizing mechanisms, like strong self-limiting population growth, allow dwarf mistletoe coexistence. Interactions shift as populations develop, and they depend largely on environmental factors such as forest structure. Intraguild mutualism is shown as a relevant process for colonization of new spaces, highlighting the complexity of competitive/facilitative interactions between parasitic plants, a formerly unexplored subject. Interactions can only be fully understood when integrating all their components at the population level. Analysing these interactions may contribute to the understanding of plant–plant interactions in general, and convey interesting implications for forest management.